Another Castle. Grimoire - Wheeler, Andrew (Comic book writer) (Oni Press, Inc., 2017)
"Princess Misty of Beldora longs for a more exciting life, but gets more than she bargained for when she is captured by Lord Badlug, the ruler of the neighboring kingdom of Grimoire. He intends to marry her and conquer Beldora, leading the land into ruin and chaos. Together with the long-suffering citizens of Grimoire and a certain bumbling prince, Misty must fight to protect her kingdom and free both realms from Badlug's tyrannical rule. Misty is determined not to be another damsel in distress ; instead, she'll discover just what it takes to be the hero of the story"--Page 4 of cover.